2023
DOI: 10.1007/s11192-023-04718-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in accounting academia: analysis from the lens of publications

Maria-Victoria Uribe-Bohorquez,
Juan-Camilo Rivera-Ordóñez,
Isabel-María García-Sánchez

Abstract: There is a significant gender gap in accounting academia that places women at a disadvantage in terms of recruitment, hiring, promotion, tenure, status, high-level areas or positions (both research and administrative), burden distribution of work, and remuneration. Women are disproportionately represented in part-time or non-tenure tracks, such as lecturers, instructors, and assistant professors. They experience a slower rate of advancement and have lower pay and prestige. Given that various authors attribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 175 publications
1
1
0
1
Order By: Relevance
“…Table 3 reports differences in the salaries and variables related to the demographics between male and female faculty members for our sample of 923 academic-year observations. Consistent with prior research (Ward 2001;Smith-Carrier et al 2021;Chen and Crown 2019;Uribe-Bohorquez et al 2023), we documented a gender pay gap, where female academics earned about CAD3000 less per year relative to their male counterparts; however, unlike prior studies, we found that this difference was not statistically significant. In terms of significant differences between the two groups, Table 3 reveals that female academics comprised about 36% of our sample, worked about 2 years less on average at the SFU, and had significantly less work experience prior to joining the SFU.…”
Section: Resultssupporting
confidence: 86%
“…Table 3 reports differences in the salaries and variables related to the demographics between male and female faculty members for our sample of 923 academic-year observations. Consistent with prior research (Ward 2001;Smith-Carrier et al 2021;Chen and Crown 2019;Uribe-Bohorquez et al 2023), we documented a gender pay gap, where female academics earned about CAD3000 less per year relative to their male counterparts; however, unlike prior studies, we found that this difference was not statistically significant. In terms of significant differences between the two groups, Table 3 reveals that female academics comprised about 36% of our sample, worked about 2 years less on average at the SFU, and had significantly less work experience prior to joining the SFU.…”
Section: Resultssupporting
confidence: 86%
“…While favoring women, they showed that the program had no harmful effects on male professors. Uribe‐Bohorquez et al (2023) evidenced that gender disparities in academia present a favorable evolution, but it is necessary to improve more equitable teams in the scientific area.…”
Section: What Know About Gender Gap In Employmentmentioning
confidence: 99%
“…Mungkin karena kami masih baru (junior) biar sekalian belajar." (Tika) Bahkan, Bohorquez, et al (2023) secara eksplisit menyatakan perempuan mengalami tingkat kemajuan yang lebih lambat dengan gaji yang lebih rendah menunjukkan secara tidak proporsional terwakili di jalur paruh waktu atau non-tenur seperti dosen, instruktur, dan asisten professor. Stereotipe perempuan yang berkaitan dengan karakteristik sifat seperti telaten dan memperhatikan detail dianggap sangat sesuai untuk mengerjakan tugas dalam profesi akuntansi (Ouenlert, 2016).…”
Section: Bagian 1: Potret Kesetaraan Gender DI Lingkungan Vokasiunclassified